Sosialisasi dan Pembentukan Koperasi Desa Merah Putih: Strategi Mewujudkan Desa Mandiri dan Sejahtera - Zahro, Khafriza Faiqotuz; Musyaffa, Mohammad Rafif; Sa’adah, Nuris; Shabila, Dinar Nimas; Yuliana, Evita Fenny; Effendi, Bahtiar (CV Global Research Publication, 2025)
This community service program aims to provide socialization and facilitate the establishment of the Merah Putih Village Cooperative in Bebel Village, Wiradesa Subdistrict, Pekalongan Regency. The initiative emerged from several fundamental problems faced by the community, such as limited access to capital, weak cooperative literacy, dependence on middlemen in agricultural distribution, and the absence of institutional governance mechanisms at the village level. The method applied was Participatory Rural Appraisal (PRA), which emphasizes community involvement from needs identification and potential mapping to decision-making. The findings reveal that the cooperative formation process is still at an early stage, with dominant issues revolving around management readiness, legal administration, and the community’s understanding of cooperative governance. Despite these challenges, the establishment of an initial management board consisting of five core members and three supervisors marks a crucial milestone toward the cooperative’s legalization and future operational sustainability. Academically, this activity contributes to the discourse on village self-reliance (Desa Mandiri) through the lens of Good Governance, highlighting that participatory decision-making, transparency in management, and community accountability are key to achieving sustainable rural economic independence. Thus, the program not only increases public awareness but also lays a governance-oriented foundation for long-term cooperative development.